(untitled) (Historia, 2021)
With Butterflies and Barbarians Patrick Harries has indeed placed under scrutiny what is announced in the subtitle to this book : Swiss Missionaries & Systems of Knowledge in South-East Africa. Although dealing to a large extent with the study and the "making" of particular African languages by the Swiss missionaries and their African assistants, this was a research project which in itself demanded thorough and painstaking mulling over numerous German and, especially, French sources from the nineteenth and early twentieth century.